The larger linear N-heteroacenes - Bunz, Uwe H. F. (Accounts of chemical research, 2015)
ConspectusThe close structural and chemical relationship of N-heteroacenes to pentacene suggests their broad applicability in organic electronic devices, such as thin-film transistors. The superb materials science properties of azaacenes result from their improved resistance toward oxidation and their potential for electron transport, both of which have been demonstrated recently. The introduction of nitrogen atoms into the aromatic perimeter of acenes stabilizes their frontier molecular orbitals and increases their electron affinity. The HOMO-LUMO gaps in azaacenes in which the nitrogen atoms are symmetrically placed are similar to those of the acenes. The judiciously placed nitrogen atoms induce an “umpolung” of the electronic behavior of these pentacene-like molecules, i.e., instead of hole mobility in thin-film transistors, azaacenes are electron-transporting materials. The fundamental synthetic approaches toward larger azaacenes are described and discussed. Several synthetic methodologies have been exploited, and some have been newly developed to assemble substituted azaacenes. The oldest methods are condensation-based. Aromatic o-diamines are coupled with o-dihydroxyarenes in the melt without solvent. This method works well for unsubstituted azaacenes only. The attachment of substituents to the starting materials renders these “fire and sword” methods less useful. The starting materials decompose under these conditions. The direct condensation of substituted o-diamines with o-quinones proceeds well in some cases. Fluorinated benzene rings next to a pyrazine unit are introduced by nucleophilic aromatic substitution employing hexafluorobenzene. However, with these well-established synthetic methodologies, a number of azaacene topologies cannot be synthesized. The Pd-catalyzed coupling of aromatic halides and aromatic diamines has therefore emerged as versatile tool for azaacene synthesis. Now substituted diaza- and tetraazaacenes, azapentacenes, azahexacenes, and azaheptacenes are accessible. Pd-catalysis-based coupling methods for both activated and nonactivated o-dihalides have been developed. The larger azaacene representatives were unknown before but are of conceptual and theoretical interest. Azaacenes, particularly the symmetrical bis(triisopropylsilylethynyl)-substituted tetraazapentacene, are primarily used in organic field-effect transistors, but smaller azaacenes shine in the field as organic light-emitting diode (OLED) emitters. Diazatetracenes and substituted benzoquinoxalines are successful, improving electron injection and increasing OLED brightness, as compared to that of pure tetracenes. On the basis of the acene framework, nitrogen atoms in the acene perimeter and aggregation-precluding molecular appendages create solid-state fluorescent species. Azaacenes are expanding the range and complementing the purview of acenes in organic electronic applications. They enlarge the profiles of acenes with respect to synthetic strategies, structures, properties, and applications.